Implementasi Building Information Modeling (BIM) Pada Proyek Perumahan - Paikun IPM; Ardin Rozandi; Dana Budiman; Indra Ramdani; Kornienko Elena Vladimirovna (Universitas Nusa Putra, 2022)
The development of the construction industry is changing very quickly. This is evidenced by the many construction projects being built in Indonesia, such as buildings, roads, bridges, etc. However, the delay in the development process is still an obstacle that must be resolved, one of which is the delay in the design process, even according to previous research, the delay based on the shop drawing process is 22%. Therefore, how to overcome delays due to the shop drawing process. Can the process of making shop drawings be more efficient? To minimize delays caused by the shop drawing design, the author will conduct research to create designs using drawing applications. By integrating Building Information Modeling (BIM) several image applications which will then be combined with estimation data and project scheduling data. Many of these applications are found on the internet, but the integration applications that I will use include Vico Office for 3D, 4D, and 5D analysis, Sketchup for architectural design, Autodesk Revit for electrical design, Tekla Structure for structural design and SAP 2000 for structure analysis. It can be concluded from this study that time efficiency can be found in making project designs and can minimize delays caused by design and planning by 30% compared to the results of design and planning that do not use the concept of integration of Building Information Modeling (BIM)